Is Obesity a Risk Factor for Periodontal Disease?: An Integrative Literature Review - , Yann Nobre Viana; , Richelly Maria Rodrigues Holanda; , Matéus Simplício Araújo; , Abrahão Lincoln Alves Cunha; , Jacques Antonio Cavalcante Maciel; , Francisco Cesar Barroso Barbosa (Archives of Current Research International, 2024)
Aims: Periodontal disease (PD) is a chronic inflammatory pathology that arises from the interaction between pathogenic bacteria and the host's immune response. The literature addresses associations of PD with other systemic conditions, such as obesity (BO). The objective of this study was to review the literature looking for scientific evidence that could clarify whether BO would be a risk factor for PD. Study Design: An integrative literature review. Methodology: The search was carried out on the VHL Regional Portal (Virtual Health Library) with articles published in English, Spanish and Portuguese. 79 articles were found between 2019 and 2024. Of this total, 63 were excluded, 1 due to duplication and 62 for not meeting the inclusion criteria. Of the studies analyzed, most report some association between obesity and periodontal disease. Thus, after reading in full, 16 articles were included. Results: The results revealed four hypotheses: a) Body mass index and waist circumference are strongly associated with an increased prevalence of PD; b) Overweight, OB and visceral adiposity index are among the main risk factors for the development of PD and the increase in its prevalence; c) PD occurs independently of metabolic syndrome (OB and overweight) and the association between PD and OB may not be so significant, even though OB presents a 15% higher risk of progression to PD; d) Although severe PD was significantly associated with OB, it was not associated with overweight. Conclusion: Therefore, most studies report a relationship between OB and PD, showing that OB plays a role in the systemic inflammation process and that it can indirectly accelerate the onset and progression of PD.